PREFERENSI PETANI TERHADAP SISTEM TANAM PADI JAJAR LEGOWO (Studi Kasus Di Desa Tambakrejo Kecamatan Patebon Kabupaten Kendal) - Nani Kusumawati; Lutfi Aris Sasongko; Rossi Prabowo (MEDIAGRO, 2015)
Paddy is the main food source for most of the population of Indonesia. The paddy crop harvested area in Patebon District in 2011 reached 2.334,47 Ha with a production of 15.603,97 tons. In Tambakrejo Village, the paddy crop harvested area in 2011 reached 132,50 Ha with a production of 861,25 tons. The purpose of this study was to determine the farmer preferences of jajar legowo paddy cropping system. The research used the descriptive method and the research location was selected by purposive method. The research location was Tambakrejo Village because farmer in thats village generally used jajar legowo cropping system. The farmer samplings were determined randomly, which was in a number of 90 respondents. The research used the tabulation analysis method and chi-square analysis. The result of this study showed that most farmers apply jajar legowo paddy cropping system with a percentage 63%, it’s mean that jajar legowo paddy cropping system have a high preferences in Tambakrejo Village. Farmer selected jajar legowo paddy cropping system because this system can facilitate the proses of fertilization, weeding and pest control, but it’s not profitable economically. This is because farmers in Tambakrejo Village do not implement the rule of recommended planting system so the production is not optimal and do not give enhancement in profits. Characteristics land area, motivation, age and education level have a significant relationship with the farmer preferences of jajar legowo paddy cropping system. Keywords: Farmer, Jajar Legowo, Preference